A Time Series Analysis of Female Labour Force Participation Rates Disaggregated by Marital Status - Walsh, William (Relations industrielles / Industrial Relations, 1982)
This paper analyzes the cyclical behavior of the labour force participation rates, adds a marital status dimension to the customary age categories generally used and includes seperate measures of the additionnal and of the discouraged worker effect.